Isolation of E. coli and Shigella spp. from raw Tilapia, elucidation of their antibiotic susceptibility pattern and evaluation of the antimicrobial efficacy of Oregano (Origanum vulgare) - Hossain, Dr. M. Mahboob (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.